ANALISIS PERBANDINGAN SISTEM INFORMASI INVENTORY MENGGUNAKAN METODE PIECES DAN MCCALL’S SOFTWARE QUALITY MODEL PADA CV. MULTI SARANA PACKINDO - Herlin Martalena Dawolo; Anton Zulkarnain Sianipar; Zulhalim Zulhalim (Smart Education, 2026)
Abstract: Inventory information systems play an important role in supporting inventory management and ensuring smooth company operations. CV. Multi Sarana Packindo has implemented an inventory information system; however, several issues are still encountered in its implementation, such as discrepancies in stock data, delays in information updates, and a system interface that does not adequately support user needs. This study aims to evaluate the performance and quality of the inventory information system at CV. Multi Sarana Packindo using the PIECES Framework and McCall’s Software Quality Model. The research method employed is descriptive qualitative, with data collected through observation, interviews, and documentation studies. The PIECES framework is used to assess the operational aspects of the system, while McCall’s model is applied to evaluate the technical quality of the software. The results indicate that the inventory information system has not yet operated optimally. The PIECES analysis reveals weaknesses in the performance, information, efficiency, and control aspects. Meanwhile, the McCall analysis shows low quality in terms of correctness, reliability, efficiency, and usability. Therefore, comprehensive improvements to both the system and business processes are required to enhance the effectiveness and accuracy of inventory management. Keywords: Inventory Information System, PIECES Framework, McCall’s Software Quality Model, System Evaluation, Software Quality Abstrak: Sistem informasi inventory berperan penting dalam mendukung pengelolaan persediaan dan kelancaran operasional perusahaan. CV. Multi Sarana Packindo telah menerapkan sistem informasi inventory, namun dalam pelaksanaannya masih ditemukan permasalahan seperti ketidaksesuaian data stok, keterlambatan pembaruan informasi, serta antarmuka sistem yang kurang mendukung kebutuhan pengguna. Penelitian ini bertujuan untuk mengevaluasi kinerja dan kualitas sistem informasi inventory pada CV. Multi Sarana Packindo menggunakan PIECES Framework dan McCall’s Software Quality Model. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan teknik pengumpulan data melalui observasi, wawancara, dan studi dokumentasi. PIECES digunakan untuk menilai aspek operasional sistem, sedangkan model McCall digunakan untuk mengevaluasi kualitas teknis perangkat lunak. Hasil penelitian menunjukkan bahwa sistem informasi inventory belum berjalan secara optimal. Analisis PIECES mengungkap adanya kelemahan pada aspek performance, information, efficiency, dan control, sementara analisis McCall menunjukkan rendahnya kualitas pada aspek correctness, reliability, efficiency, dan usability. Oleh karena itu, diperlukan perbaikan menyeluruh pada sistem dan proses bisnis untuk meningkatkan efektivitas dan akurasi pengelolaan persediaan. Kata kunci: Sistem Informasi Inventory, PIECES Framework, McCall’s Software Quality Model, Evaluasi Sistem, Kualitas Perangkat Lunak